Substance dependence and pregnancy - Bilge, Ayşegül; Savaşan, Ayşegül; Zorlu, Mehtap; Erkman, Zeynep (Journal of Dependence, 2010)
Dependence is a disease that has biological, social and behavioral dimension. Substance use during pregnancy effects negatively both of pregnant and fetus. The use of tobacco products during pregnancy makes prenatal mortality and morbidity doubled. Alcohol use during pregnancy can cause fetal alcohol syndrome (FAS) and fetal alcohol spectrum disorders (FASB). Heavy caffeine consumption during pregnancy can cause adverse effects such as spontaneous abortion. Pregnants meet generally more with nurses and midwives in health institution. Therefore, these professionals must be informed of consulting services related to substance dependence. The aim of this article is to show that substance use during pregnancy has negative effects on pregnant and fetus and to submit appropriate care principles.